2021
DOI: 10.1007/s40368-020-00596-w
|View full text |Cite
|
Sign up to set email alerts
|

Dense bone islands in pediatric patients: a case series study

Abstract: Background Dense Bone Islands (DBIs) are anatomic variants defined as radiopaque lesions consisting of hamartomatous cortical bone, often presenting as incidental radiographic findings. DBIs can also be known as idiopathic osteosclerosis, bone whorl, focal periapical osteopetrosis, bone scar and enostosis. We found a paucity of literature for management and reporting of this condition in children. For this reason, the authors describe sixteen cases of children and adolescents with dense bony isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In addition, it is necessary to monitor DBI, regular radiographic reports (as in the case of orthodontic treatment), and careful treatment measures to prevent potential damage to the teeth and surrounding area. 13,18 CONCLUSION Based on the results of the research conducted, it can be concluded that the most classification of DBI based on radiopaque area was found in type 5 separate with the most locations located in the premolar region. While the least classification was found in type 2 interradicular and separate with the least locations located in two locations, there were on the incisive region and the incisive-canine region.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, it is necessary to monitor DBI, regular radiographic reports (as in the case of orthodontic treatment), and careful treatment measures to prevent potential damage to the teeth and surrounding area. 13,18 CONCLUSION Based on the results of the research conducted, it can be concluded that the most classification of DBI based on radiopaque area was found in type 5 separate with the most locations located in the premolar region. While the least classification was found in type 2 interradicular and separate with the least locations located in two locations, there were on the incisive region and the incisive-canine region.…”
Section: Discussionmentioning
confidence: 90%
“…One of the orthodontic treatment cases studied by Alfahad et al 18 showed that type 4 apical DBI caused mesial root resorption in tooth 46 and suggested further monitoring during orthodontic treatment. The study by Dananjaya Agung & Lestarini 19 also found DBI with type 4 apical in the periapical area of tooth 48 that did not erupt completely (impacted), indicating that DBI could block tooth eruption even in the jaws that had sufficient space for eruption.…”
Section: Discussionmentioning
confidence: 99%
“…Cementoblastoma (previously described in the literature as cementomas, true cementomas, sclerosing cementomas, periapical fibro-osteoma and periapical fibrous dysplasia) is a rare benign odontogenic tumour of mesenchymal origin [16]. It is diagnosed in young female patients, predominantly between 20 and 30 years of age, with a slight male predominance [17].…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic Osteosclerosis (IO), also known as Dense bone island (DBI), is de ned as the non-expansive, localized accumulation of trabecular bone within cancellous bone tissues. Even though the etiologic factors of IO formation have not been assumed yet, bone reaction related to increased occlusal forces, the stimulating effect of residual root fragmentation and adequate blood supply, and torus-like developmental anatomic variations have been discussed as possible causes of IO formation (1)(2)(3)(4). consists of 300 cases, including the rst consecutive 150 men and 150 women of the year 2021 tting our inclusion criteria, aging from 8 to 85 years (20).…”
Section: Introductionmentioning
confidence: 99%